Carbon Emissions on Firm Value: Evidence from Energy Sector Companies in Indonesia - Fawzyputra Valentino Rizqy; Dewi Veni Soraya; Pramita Yulinda Devi (E3S Web of Conferences)
Industry is currently developing rapidly along with the increase in human resource population and technological developments. The factor that influences firm value is environmental responsibility. The aim of this research is to analyze the influence of Environmental Performance, Implementation of Green Accounting, Disclosure of Sustainability Reports and Disclosure of Carbon Emissions on Firm Value. The population in this study are energy companies listed on the Indonesia Stock Exchange in 2018-2022. The research sample was 12 companies, so the total number of samples obtained over 5 years was 60 samples. This research uses quantitative methods, using secondary data. Data analysis techniques and hypothesis testing using SPSS software. The method used for this research is multiple linear regression. The research results show that better environmental performance will increase firm value, while the implementation of green accounting, disclosure of sustainability reports, and disclosure of carbon emissions has no effect on firm value. This research has the implication that companies should increase environmental responsibility due to the impact of company activities.